1994
DOI: 10.1210/endo.135.2.8033823
|View full text |Cite
|
Sign up to set email alerts
|

Role of the capacitative calcium influx in the activation of steroidogenesis by angiotensin-II in adrenal glomerulosa cells.

Abstract: Angiotensin-II (AngII)-induced Ca2+ influx in adrenal glomerulosa cells, a signal necessary for the stimulation of steroidogenesis by the hormone, is believed to involve two distinct mechanisms: 1) opening of voltage-operated Ca2+ channels, and 2) activation of a capacitative Ca2+ entry pathway that is dependent on calcium release from intracellular stores. Nicardipine, a dihydropyridine calcium antagonist, has been used to investigate the role of these Ca2+ entry mechanisms in the steroidogenic response to An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Together these data indicate that Ang II-stimulated StAR promoter activity is not dependent upon reaching a threshold level of [Ca 2ϩ ] i . Previous studies reported Tg increased aldosterone production in both primary cultures of bovine and rat adrenal glomerulosa cells (5,39,40). However, a significant Tg response in bovine adrenal cells required 8 mM K ϩ in the medium, and our culture conditions had 4 mM K ϩ , which may account for the difference.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Together these data indicate that Ang II-stimulated StAR promoter activity is not dependent upon reaching a threshold level of [Ca 2ϩ ] i . Previous studies reported Tg increased aldosterone production in both primary cultures of bovine and rat adrenal glomerulosa cells (5,39,40). However, a significant Tg response in bovine adrenal cells required 8 mM K ϩ in the medium, and our culture conditions had 4 mM K ϩ , which may account for the difference.…”
Section: Discussionmentioning
confidence: 73%
“…Depletion of the intracellular calcium stores activates capacitative calcium entry, thus Ang II mediates an influx of external Ca 2ϩ via calcium release activated calcium (CRAC) channels (3,4). Although Ang II has been shown to activate voltage-gated calcium channels, this pathway is not considered a major contributor to the steroidogenic response (5). K ϩ activation of aldosterone synthesis, on the other hand, is associated with an influx of external Ca 2ϩ via voltage-gated Ca 2ϩ channels (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The emptying of calcium stores triggers 'capacitative' Ca2+ entry by a yet unknown mechanism. Yet the calcium signal in response to angiotensin I1 is larger than that induced by thapsigargin, suggesting an additional calcium entry pathway (Burnay et al, 1994).…”
Section: Cell Signalling For Aldosterone Synthesismentioning
confidence: 94%
“…, 1991), which appears to be mediated by protein kinase C (PKC) and to lead to stimulation of Ca2+ influx through T channels. Nicardipine, at concentrations which block both T-and L-calcium channels, reduces only to a minor degree the calcium and aldosterone responses to angiotensin 11, again pointing to a dual mechanism of intracellular calcium elevation in response to angiotensin I1 (Burnay et al, 1994). Finally, angiotensin I1 in single bovine glomerulosa cells has been found to induce cytosolic free calcium oscillations which are dependent on the presence of extracellular calcium (Johnson et al, 1989).…”
Section: Cell Signalling For Aldosterone Synthesismentioning
confidence: 95%